(untitled) (Texas Journal of Medical Science, 2026)
Asthma attack is a severe and life-threatening condition of bronchial asthma, manifesting in children as acute difficulty in breathing. The disease primarily occurs due to inflammation of the bronchial mucosa, bronchospasm, and increased mucus production. Symptoms include shortness of breath, coughing, chest tightness, and fainting. Asthma attacks require urgent medical attention because delays can lead to oxygen deficiency and life-threatening complications in children. Prevention involves proper management of bronchial asthma, avoiding allergens, and correct use of inhalers and bronchodilator medications